2010
DOI: 10.1007/s00417-010-1371-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of the complement factor H mRNA in proliferating human RPE cells

Abstract: The identification of the differential expression of the regulatory factors H and I of the complement system in cultured RPE cells by a technique without any prerequisites demonstrates and confirms the importance of these factors in RPE cells. In addition to its known role in age-related macular degeneration, the presence of these complement factors in epiretinal membranes may also indicate a role of the complement system in proliferative retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Wang et al showed that a component of drusen, amyloid beta, can bind to CFI and consequently reduce its function, potentially leading to chronic low-grade inflammation ). However proliferating RPE cells, also seen in early AMD, demonstrate increased expression of CFI protein (Kociok and Joussen 2010). RPE hypertrophy may be a response to inflammation, and increased CFI levels may be induced as a compensatory response.…”
Section: Complement Factor Imentioning
confidence: 95%
See 1 more Smart Citation
“…Wang et al showed that a component of drusen, amyloid beta, can bind to CFI and consequently reduce its function, potentially leading to chronic low-grade inflammation ). However proliferating RPE cells, also seen in early AMD, demonstrate increased expression of CFI protein (Kociok and Joussen 2010). RPE hypertrophy may be a response to inflammation, and increased CFI levels may be induced as a compensatory response.…”
Section: Complement Factor Imentioning
confidence: 95%
“…In vitro studies show an increase in RPE CFH production by interferon-gamma (Kim et al 2009), and reduction in conditions of oxidative stress ). In addition, CFH secretion is associated with in vitro RPE migration and hypertrophy, suggesting the RPE proliferation seen in AMD may be accompanied by a compensatory increase in complement regulatory factors (Kim et al 2009;Kociok and Joussen 2010).…”
Section: Local Intraocular Cfh and Amdmentioning
confidence: 95%
“…Concurrently, this activation stimulates the age-induced response of augmented synthesis of endogenous CRMs, such as CFH [ 21 , 22 ] or CFB [ 20 ]. Moreover, Kociok and Joussen observed that human RPE cells that are stimulated to proliferate in culture conditions express CRMs, such as CFH and CFI, at the mRNA and protein levels [ 23 ]. Interestingly, in cultured human and murine RPE cells, the membrane-bound CRMs, such as CD46, CD55, and CD59, were also shown to be specifically upregulated by inflammatory cytokines, including IFN- γ , TNF- α , and IL-1 β , as well as by repetitive nonlethal exposure to oxidative stress [ 24 ].…”
Section: Biology Of Complement System In Retinamentioning
confidence: 99%
“…Non-coding RNA consists of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs). Recent epigenetic and genetic evidence has indicated that miRNAs, such as miR-146A, miRNA-9, miRNA-155 and miRNA-125b are upregulated to modulate a family of potentially pathogenic genes involved in Alzheimer's disease and cancer (17)(18)(19)(20). In 2011, Salmena et al (21) proposed a competing endogenous RNA (ceRNA) hypothesis, which is now supported by further evidence (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%